Problems of sparing surgery for otosclerosis - O. N. Sopko; V. V. Diskalenko (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2013)
The article deals with optimization of the current technical methods in operations on the osteosclerotic stapes aimed at minimization of any trauma in the inner ear and at maximal possible safety for the sound-conducting structures - the factors that guarantee the functional results of the surgery.